Service innovation Integrated Public NTPD 112 In Supporting Sombere ' Smart City' in Makassar City - Muh. Rizal Suyuti; A. Rismawinardi Nur (Universitas Negeri Makassar, 2026)
This study aims to evaluate the effectiveness of NTPD 112 public services in supporting the implementation of Sombere' Smart City in Makassar City, using the theory of service responsiveness. NTPD 112 is an emergency service provided to respond to public reports quickly and effectively. In this study, various indicators of service responsiveness were analyzed, including response time, speed of resolution, quality of interaction, level of problem solving, service accessibility, and customer satisfaction. Qualitative research methods were used through a library research approach and literature studies combined with field data analysis through interviews and surveys of respondents who use the NTPD 112 service. The results showed that NTPD 112 performed quite well in responding to emergency reports with an average response time of 7 minutes. However, there were several obstacles in handling non-emergency reports, especially in terms of coordination between agencies and service accessibility in certain areas. Public satisfaction with NTPD 112 services reached 75%, reflecting a positive response even though there were several areas of improvement, such as improving officer communication skills and developing a more accessible reporting system. Recommendations are provided to optimize response time and quality of interaction through the use of information technology and officer training. Overall,